High-grade serous carcinoma with discordant p53 signature: report of a case with new insight regarding high-grade serous carcinogenesis - Yuichiro Hatano; Shinya Fukuda; Hiroshi Makino; Hiroyuki Tomita; Ken-ichirou Morishige; Akira Hara (BMC, 2018)
Abstract Background Although p53 signature, benign-appearing epithelial cells with p53 diffuse expression, is frequently found in the fallopian tubes, the clinical and pathological significance of this lesion in the case of high-grade serous carcinoma (HGSC) patients still remains unclear. Case presentation A 56-year-old woman was referred to the gynecologist on account of abdominal distention. Since radiological and serological workup suggested that her illness was due to advanced ovarian cancer (FIGO Stage IVB), she received neoadjuvant chemotherapy, and the clinical evaluation of the chemotherapeutic response was a partial response. She underwent total hysterectomy with bilateral salpingo-oophorectomy, omentectomy, and intra-pelvic and para-aortic lymphadenectomy. Histologically, the cancer cells showed high-grade nuclear atypia and spread into the bilateral ovaries, omentum, uterine serosa, and left fallopian tube. The cancer cells showed complete absence of p53 but overexpressed p16, whereas some of benign-appearing tubal epithelial cells overexpressed p53 but lacked p16 expression. The results of direct sequence analysis revealed that the ovarian cancer contains a 1 bp deletion in exon 8 of TP53. Finally, the histological diagnosis of HGSC with discordant p53 signature was made. Interestingly, nuclear expression of γ-H2AX, a well-known marker of DNA damage, was not only observed in both p53 aberrantly-expressing lesions but also the benign-appearing tubal epithelium without p53 overexpression. After the histological confirmation, she received adjuvant chemotherapy and has been in disease-free condition without any detectable tumor for 5 months. Conclusion Recent evidence suggests that p53 signature is the putative precursor of p53 overexpression-type HGSC. Because the putative precursors of the other p53 immunophenotypical HGSC are not proposed, we presume γ-H2AX-expressing cells without p53 overexpression may be a potent candidate of null-type TP53-mutated tubal cells, which are named "γ-H2AX responsive foci."